Association between obesity and medical expenditures among Japanese adults treated for diabetes: A secondary analysis - Yuki Yonekura; Kozo Tanno; Aya Higashiyama; Nagako Okuda; Tomomi Nagahata; Akira Okayama (PLoS ONE, 2026)
In Japan, where obesity prevalence is lower than in Western countries, few studies have examined the association between obesity and medical expenditures among patients with diabetes, distinguishing between overweight and obesity by sex. This study examined the association between obesity and medical expenditures among patients with diabetes in Japan. Data on medical expenditures and the Specific Health Checkups obtained from 12 municipal and six union insurers for fiscal years 2008 and 2009 were analyzed. Gamma regression and quantile regression were used to compare annual total, outpatient, and inpatient medical expenditures in fiscal year 2009 among three groups: normal/underweight (body mass index [BMI] < 25 kg/m 2 ), overweight (BMI: 25–30 kg/m 2 ), and obesity (BMI ≥ 30 kg/m 2 ). The analyses were performed separately for men and women, adjusting for age, hypertension, hyper-low-density lipoprotein cholesterolemia, glycemic control, and smoking. Logistic regression was performed, adjusting for the same variables to assess the occurrence of annual total medical expenditures of ¥1 million (approximately US$10,600 in 2009) or more. Annual total medical expenditures were significantly higher in the obesity group than in the normal/underweight group among both men and women (exp(β) = 1.117 [95% confidence interval (CI): 1.023–1.221] among men and exp(β) = 1.157 [1.036–1.295] among women). Both men and women in the overweight and obesity groups had significantly higher outpatient expenditures than those in the normal/underweight group. The overweight and obesity groups had significantly higher medical expenditures than the normal/underweight group in most quantiles among men. The likelihood of annual total medical expenditures exceeding ¥1 million was higher among women with obesity than among those with normal/underweight (odds ratio = 1.546 [95% CI: 1.007–2.375], p = 0.047). These findings suggest that medical expenditures among patients with diabetes who have overweight or obesity are higher than those of normal/underweight patients.